Meta-Symbolic Simulation System (Messy) User Manual with Forward: The History of Messy - Appelbaum, Matthew; Klein, Sheldon (University of Wisconsin-Madison Department of Computer Sciences, 1976)
User manual for the meta-symbolic simulation system that includes a behavioral simulation programming language that models, generates and manipulates events in the notation of a semantic network that changes through time, and a generalized, semantics-to-surface structure generation mechanism that can describe changes in the semantic universe in the syntax of any natural language for which grammar is supplied. The system can handle generative semantic grammars in a variety of theoretical frameworks, and is especially suited for modelling text grammars, including "frames", "scripts", and "scenarios". While Sheldon Klein is responsible for the basic design of the system, it is the result of the efforts of more than twenty students, over a five year period.